Efficacy of dental floss as an adjunct to toothbrushing in dental plaque and gingivitis: An open-labeled clinical nonexperimental study - Shrikanth Muralidharan; Arunkumar Acharya; Pramila Mallaiah; Shanthi Margabandhu; Sakharam Garale; Mayur Giri (Wolters Kluwer Medknow Publications, 2019)
Background: Periodontitis presents itself in the form of gingivitis or periodontal pockets/periodontitis. Gingivitis always precedes the later, but the reverse may not be true. Dental plaque is the primary etiology for chronic gingivitis. Hence, a regular cleaning is necessary especially in the interdental areas for the removal of plaque and to prevent gingivitis and periodontitis by means apart from the regular brushing. The most common and affordable ways of achieving this are through the use of dental floss. Aim: The present study was carried out to evaluate the effect of flossing with a waxed dental floss apart from toothbrushing as an effective means to reduce gingival inflammation. Materials and Methods: The study was an open-labeled nonexperimental clinical study. A total of 60 adult patients between 20 and 50 years were selected and randomly assigned to 2 groups - one Group A with only manual toothbrushing (Oral B) and the Group B with manual toothbrushing (Oral B) and flossing with an unwaxed dental floss (Colgate). Both the groups were evaluated at baseline, after 14 days and after 28 days. Gingival index was recorded using the Loe and Sillness index while the gingival bleeding was scored using the Carter and Barnes Bleeding Index. The data collected were subjected to statistical analysis using SPSS 20.0 (Chicago, IL, USA). Student's "t"-test was carried out. All P < 0.05 were considered to be statistically significant. Results: There was a statistically significant reduction in the gingivitis, bleeding, and plaque accumulation in the Group B compared to Group A, at baseline and after 28 days of evaluation (P < 0.001). There was no significant reduction in the bleeding index for the lingual surfaces between the two groups. The results thus showed that there was a significant reduction in the plaque accumulation and gingival bleeding for Group B compared to Group A. Conclusion: Regular toothbrushing helped to improve the gingival health and reduce the amount of plaque accumulation. Toothbrushing and flossing served better in achieving interdental plaque control and in reducing gingival bleeding.